Open-source ERP adoption of SMEs a study on the readiness of some Philippine Small and Medium-sized Enterprises - Chung, Nelson (University of the Philippines Diliman, 2009)
Enterprise resource planning (ERP) software has been traditionally adopted only by the large enterprises due to its large investment, and has been a source of competitive advantage. Due to the vital role small and medium-sized enterprises (SMEs) play in economic development, it is important to make these SMEs competitive, and what better way than for these SMEs to adopt ERP. This study focuses on the assessment of SMEs' readiness to adopt affordable open-source ERP software, instead of the proprietary ERP software. In line with this assessment, information related to open-source adoption were gathered from SMEs. To guide this assessment, a conceptual framework and questionnaire guide was developed by examining three known adoption theories, Technology Acceptance Model, Innovation Diffusion Theory and Technology-Organization-Environment framework. The resulting framework consisted of 4 dimensions, namely : Technological dimension, Organizational dimension, Environmental dimension and Individual dimension. ERP systems are highly sophisticated information system which can provide efficiency and competitive advantage to firms that adopts it. Aside from proprietary software, ERP software has already been invaded by open-source software which provides an alternative to the most expensive SAP and Oracle. SMEs comprise 99.7 percent of the established businesses in the Philippines and provide almost 67 percent employments in the entire nation. However, SMEs are not as competitive against their ICT-enabled counterpart in highly-developed countries. It has been identified that lack of financing and equipment and low priority are amongst the highest barriers for ICT adoptions. Based on the case studies, it has been identified that lack of awareness pose as the primary potential barrier for ERP adoption. This is followed by the SMEs focus on return on IT investments as well as sensitivity to cost/price. The output of this study will provide government agencies and IT vendors insights to ERP adoption and will allow them to have a well-informed long-term strategy formulation.